1978
DOI: 10.1002/art.1780210204
|View full text |Cite
|
Sign up to set email alerts
|

Effect of altered lymphocyte function on immunologic disorders in nzb/nzw mice.

Abstract: Administration of thymosin fraction V to NZB/NZW F1 mice, an animal model for human SLE, accelerated the appearance of proteinuria and anti‐nDNA antibodies, increased deposition of immunoglobulins in kidneys, and significantly shortened survivals. Although the addition of thymosin to in vitro cultures of spleen and lymph node cells from thymosin‐treated mice increased DNA synthesis in response to stimulation with Con A, in vivo treatment with thymosin did not affect the Con A response. There was no effect on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

1979
1979
1983
1983

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 41 publications
0
4
1
Order By: Relevance
“…The NZB mouse spleen cells, however, exhibited no potentiated responses even when precultured with thymosin, and the nu/nu mouse spleen cells showed a slightly potentiated response only to Con A. Many investigators have shown the effects of thymosin on the mitogens of mouse spleen cells (Rotter and Trainin 1975;Thurman and Goldstein 1976), purporting that thymosin potentiated the responses of the CS,Bl and BALB/C mouse spleen cells, and that thymosin gave the same effect as revealed in this study on the NZB/W and nu/nu mouse spleen cells or an effect which was contrary to the latter (Gershwin et al 1974; Ikehara et al 1975;Mehta et al 1978).…”
Section: Thy 1 Antigen Positive Cellscontrasting
confidence: 34%
“…The NZB mouse spleen cells, however, exhibited no potentiated responses even when precultured with thymosin, and the nu/nu mouse spleen cells showed a slightly potentiated response only to Con A. Many investigators have shown the effects of thymosin on the mitogens of mouse spleen cells (Rotter and Trainin 1975;Thurman and Goldstein 1976), purporting that thymosin potentiated the responses of the CS,Bl and BALB/C mouse spleen cells, and that thymosin gave the same effect as revealed in this study on the NZB/W and nu/nu mouse spleen cells or an effect which was contrary to the latter (Gershwin et al 1974; Ikehara et al 1975;Mehta et al 1978).…”
Section: Thy 1 Antigen Positive Cellscontrasting
confidence: 34%
“…AntiDNA antibody production, especially that of antiDNA antibodies of the IgG class, starts very early in life and is highly sensitive to the activity of helper T cells in female B/W mice, since neonatal thymectomy reduces it to the level of male B/W mice (33). Therefore, the increase of anti-DNA antibody under T cell stimulation is not an unexpected result and might contribute to the aggravation of the renal lesions often reported in B/W mice undergoing T cell stimulation (32,34,35).…”
Section: Discussionmentioning
confidence: 92%
“…Treatment with other thymic factors (such as thymosin, T cell replacement by grafting syngeneic thymocytes, or spleen cells) or treatment with T cell factors (secreted following stimulation by Con A) also failed to diminish antiDNA antibody production in NZ mice and even augmented it (31,32). AntiDNA antibody production, especially that of antiDNA antibodies of the IgG class, starts very early in life and is highly sensitive to the activity of helper T cells in female B/W mice, since neonatal thymectomy reduces it to the level of male B/W mice (33).…”
Section: Discussionmentioning
confidence: 99%
“…Graft-versus-host reactions were measured by a modified Simonsen assay as described previously (16,17).…”
Section: Methodsmentioning
confidence: 99%
“…Antibodies to SRBC and to SSSZII (subject to macrophage and helper T cell control and suppressor T cell control, respectively) were measured by enumerating plaque forming cells in spleens from immunized mice by incubating these cells with SRBC or SSSIII coated SRBC, as described previously (16,18,19).…”
Section: Methodsmentioning
confidence: 99%